2005
DOI: 10.1007/s10620-005-2552-6
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Referral Patterns of Primary Care Physicians When Evaluating Subjects with Noncardiac Chest Pain?A National Survey

Abstract: Noncardiac chest pain (NCCP) may affect up to 23% of the U.S. population. The clinical approach and referral patterns of primary care physicians (PCPs) when evaluating NCCP subjects are unknown. We aimed to determine the preferences of diagnostic tests, referral patterns, and treatment plans of NCCP patients by PCPs. PCPs were randomly selected from the American Medical Association national membership list. A 24-item questionnaire was mailed, which focused on demographic information, characteristics of practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
3
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 22 publications
1
17
3
1
Order By: Relevance
“…Although repeated ED visits for chest pain are to be expected, the number of repeated cardiology evaluations and the paucity of GI consultations are surprising. Our result is in direct contradistinction to results from a survey by Wong et al 24 of 205 primary care physicians in the United States. These investigators reported that, when referring patients for further management of NCCP, most primary care physicians preferred consultation by a gastroenterologist (75.6%) and less frequently asked for consultation by a cardiologist (7.8%).…”
Section: Gi Testingcontrasting
confidence: 99%
“…Although repeated ED visits for chest pain are to be expected, the number of repeated cardiology evaluations and the paucity of GI consultations are surprising. Our result is in direct contradistinction to results from a survey by Wong et al 24 of 205 primary care physicians in the United States. These investigators reported that, when referring patients for further management of NCCP, most primary care physicians preferred consultation by a gastroenterologist (75.6%) and less frequently asked for consultation by a cardiologist (7.8%).…”
Section: Gi Testingcontrasting
confidence: 99%
“…[17][18][19][20] It is also uncertain whether chest X-ray is useful in evaluating the cause of NCCP in the absence of coexisting pulmonary symptoms such as cough, haemoptysis, shortness of breath and other symptoms. 8 Although not being used commonly as first-line test, specialized oesophageal testing such as 24 h pH study, manometry, barium swallow and Bernstein test were being used in quite a number of cases. This may reflect the complex nature of the cases being seen by the gastroenterologist but it may also suggest an excessive use of tests trying to find ⁄ exclude the cause for the chest pain.…”
Section: Discussionmentioning
confidence: 99%
“…A maioria dos pacientes é diagnosticada e tratada por médicos clínicos, com apenas 17% dos pacientes encaminhados para o gastroenterologista (44) (Figura 1).…”
Section: Epidemiologiaunclassified